2015
DOI: 10.1016/j.camwa.2015.01.010
|View full text |Cite|
|
Sign up to set email alerts
|

A D3Q27 multiple-relaxation-time lattice Boltzmann method for turbulent flows

Abstract: a b s t r a c tA three-dimensional twenty-seven (D3Q27) discrete velocity multiple-relaxation-time lattice Boltzmann method is developed. The proposed scheme is validated in fully developed turbulent channel, pipe and porous medium flows through direct and large eddy simulations. The direct numerical simulation of the turbulent channel flow confirms that the present scheme is as reliable as the spectrum method for simulating turbulence. Through the large eddy simulations of the pipe and porous medium flows, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(99 citation statements)
references
References 36 publications
4
95
0
Order By: Relevance
“…These matrices are derived similarly as in Refs. [73][74][75]; the only difference here concerns the ordering indexes i of the velocity space which is different from these studies. It has been judged pertinent to reproduce them in the present article so that all the matrices and indexes are presented here with the same ordering of the lattice connectivity vectors.…”
Section: A Single-phase Collision Operatormentioning
confidence: 76%
“…These matrices are derived similarly as in Refs. [73][74][75]; the only difference here concerns the ordering indexes i of the velocity space which is different from these studies. It has been judged pertinent to reproduce them in the present article so that all the matrices and indexes are presented here with the same ordering of the lattice connectivity vectors.…”
Section: A Single-phase Collision Operatormentioning
confidence: 76%
“…Furthermore, it is found that the nonorthogonal MRT-LBM requires approximately 25% less computational time than the orthogonal MRT model in Ref. [48]. …”
Section: Appendix C: Nonorthogonal Mrt-lbm For 3d Lid-driven Cavity Flowmentioning
confidence: 99%
“…Therefore, compared with the D3Q27 MRT-LBM in Ref. [48], an MRT-LBM based on the present raw moment set can simplify the implementation and reduce the computational cost. As shown in Appendix C, the simulation results for 3D Lid-driven cavity flow by the nonorthogonal MRT-LBM are in good agreement with the benchmark solutions by Ku et al [49], which implies that the nonorthogonal MRT-LBM can retain the numerical accuracy when simplifying the implementation.…”
Section: B Central Moment Set Equilibria and Forcing Termsmentioning
confidence: 99%
See 1 more Smart Citation
“…The porous wall consists of staggered cube arrays in which solid cubes are interconnected and the porosity of the porous wall is set to 0.71. To directly treat the porous structure, the D3Q27 multiple relaxation time (MRT) lattice Boltzmann method (LBM) of Suga et al (2015) with the imbalance correction local grid refinement method of Kuwata and Suga (2016) is employed for the turbulent flow simulation.…”
Section: Introductionmentioning
confidence: 99%